Are Londoners Prepared for an Emergency? A Longitudinal Study Following the London Bombings - Page, Lisa (Mary Ann Liebert, Inc., 2008)
The UK government sees increasing individual preparedness as a priority, but the level of preparedness of people in the UK for a large-scale emergency is not known. The London bombings of July 7, 2005, affected many Londoners and may have altered their sense of vulnerability to a future terrorist attack. We used a longitudinal study design to assess individual preparedness within the same sample of Londoners at 2 points in time: immediately after the bombings (T(1)) and 7 to 8 months later (T(2)). A demographically representative sample of 1,010 Londoners participated in a phone interview at T(1). Subsequently, at T(2), 574 of the same people participated in a follow-up phone interview. At T(1) 51% of Londoners had made 4 or more relevant emergency plans; 48% had gathered 4 or more relevant supplies in case of emergency. There was evidence of increased preparedness at T(2), by which time 90% had made 4 or more emergency plans. Ethnicity, low social status, and having felt a sense of threat during the bombings predicted increased preparedness between T(1) and T(2). Women in general, and women of low social status in particular, perceived themselves to be unprepared in the event of a future terrorist attack. In summary, Londoners show moderate levels of emergency preparedness, which increased following the London bombings. Although we cannot know whether this association is causal, the prospective nature of the study increases the likelihood that it is. However, preparedness is still patchy, and there are important demographic associations with levels of preparedness and perception of vulnerability. These findings have implications for future development of individual and community emergency preparedness policy.